STUDI KOMPARATIF TENTANG MEKANISME PASAR IBNU KHALDUN DAN ADAM SMITH - Muhammad Arifin (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2016)
This article was aimed to explain the nature of market mechanism in prespective of Ibnu Khaldun and Adam Smith. Historical dan philosophical approach were used in the analysis to oversee Ibnu Khaldun and Adam Smith basic teaching on market and to explore ideas of both. The article concluded that within theory ofÂ price, theory of value, division of labour, nation/government. Market mechanism that protect people ofÂ the right and just price has also been considered as important and neccesary for better life. This then implied the need to keep market mechanism work which was part ofÂ government duties.